Additional observations on the biogeography of the Amotape-Huancabamba zone in Northern Peru: Defining the South-Eastern limits - Weigend, Maximilian (2004)
Data from Loasaceae and Ribes (Grossulariaceae) obtained during field studies in Peru allow us to define the southeastern limit of the Amotape-Huancabamba Zone with remarkable precision. The limit runs in slightly southeasterly direction from NE of Otuzco (department La Libertad, province Otuzco, Río Chicama drainage system: S 07° 50,315´, W 078° 29,076´) to the mountain pass between Parcoy and Buldibuyo (department La Libertad, province Pataz, N of the Río Cajas: S 08° 04,619´, W 077° 25,457´). The plant groups typical of the Amotape Huancabamba Zone (N. triphylla group, N. ser. Alatae, Ribes andicola group, Nasa picta subsp. picta) find their southeastern distribution limit in the northern part of the province Pataz, and are replaced by their southern counterparts (N. poissoniana group, Ribes viscosum) immediately south of this pass height.